2005
DOI: 10.1182/blood-2005-02-0508
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of individuals with pure red cell aplasia and antierythropoietin antibodies in patients treated with recombinant epoetin: a follow-up report from the Research on Adverse Drug Events and Reports (RADAR) Project

Abstract: Since its introduction in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 30 publications
1
64
1
Order By: Relevance
“…Therefore, in our case, the induction of autoimmunity to the pegylated glycoprotein is the most probable pathogenesis of PRCA development including the inhibition of erythropoiesis, although we cannot exclude other possibilities because PRCA itself is an incidental complication in HD patients [11]. Regarding the treatment of PRCA associated with ESA therapy, it has previously been reported that PRCA did not improve without immunosuppressive treatment [21]. The largest retrospective study, including 47 patients with PRCA, reported that renal transplantation, corticosteroids, cyclosporine, and corticosteroids in combination with cyclophosphamide were considered effective therapies [22].…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, in our case, the induction of autoimmunity to the pegylated glycoprotein is the most probable pathogenesis of PRCA development including the inhibition of erythropoiesis, although we cannot exclude other possibilities because PRCA itself is an incidental complication in HD patients [11]. Regarding the treatment of PRCA associated with ESA therapy, it has previously been reported that PRCA did not improve without immunosuppressive treatment [21]. The largest retrospective study, including 47 patients with PRCA, reported that renal transplantation, corticosteroids, cyclosporine, and corticosteroids in combination with cyclophosphamide were considered effective therapies [22].…”
Section: Discussionmentioning
confidence: 75%
“…For NSF, reports of a gadodiamide-NSF relationship from Austria and Denmark were published three months apart and for PRCA, reports from the United States/Europe and Canada were published on the same day. 5,43,50,51 For RS, a preliminary report of the Arizona case-control study in the Morbidity and Mortality Weekly Report in July 1980 was followed by preliminary and final reports of Michigan and Ohio studies with similar findings six and 18 months later, respectively. 22-25 Regulatory responses were delayed and uncoordinated.…”
Section: Discussionmentioning
confidence: 99%
“…50 In 2005, the groups collaboratively reported that epoetinassociated PRCA disappeared following renal transplantation. 51 In 2009, epoetin-associated PRCA resolved in 13 of 14 patients who received a novel peptide-based erythropoietin-receptor agonist. 52 PRCA from increased use of subcutaneous epoetin was facilitated by several factors (Table 1).…”
Section: Pure Red Cell Aplasiamentioning
confidence: 99%
“…Bennett et al (27) reported recovery rates from PRCA of 2% without immunosuppressive therapy, 52% after immunosuppressive treatment(s) outside the renal transplantation setting, and 95% after kidney transplantation. The relative importance of immunosuppression and normalization of kidney function after kidney transplantation in resolving ESA-induced PRCA has not been established.…”
Section: Treatment Of Esa-induced Prcamentioning
confidence: 99%